Trajectories of anxiety and depression among Chinese men who have sex with men on pre-exposure prophylaxis: a group-based trajectory model approach - Shuo Chen; Yan-Yan Zhu; Zhen-Xing Chu; Hui Zhou; Miao Liu; Yong-Jun Jiang; Qing-Hai Hu; for the China Real-World Oral Intake of PrEP (CROPrEP) Study Team (BMC Public Health, 2024)
Abstract Background Anxiety and depression can influence adherence to Pre-exposure Prophylaxis (PrEP). However, there is limited research on the temporal dynamics of anxiety and depression among men who have sex with men (MSM) using PrEP. Methods From December 2018 to November 2020, we administered the Hospital Anxiety and Depression Scale (HADS) to participants in the China Real-World Oral Intake of PrEP (CROPrEP) to measure their anxiety and depression levels. The group-based trajectory model (GBTM) depicted the dynamic changes of anxiety and depression scores over time. Results A total of 1023 MSM were included, with 4523 follow-up assessments. The GBTM categorized the trajectories into three distinct patterns: consistently low (54.8% for anxiety, 60.7% for depression), consistently moderate (39.3% for anxiety, 31.4% for depression), and high but bell-shaped (5.9% for anxiety, 7.9% for depression). Higher anxiety levels were associated with being aged 18–30 years old, earning less than US$619 per month, female-identifying, adopting the bottom sexual role with men, and having two or more anal sex partners in the past three months; similarly, higher depression levels correlated with a monthly income under US$619, female-identifying, sexual behavior as bottom and a positive syphilis at baseline. PrEP adherence was notably lower in the high but bell-shaped anxiety and depression group compared to the other groups, particularly at the 12th-month follow-up. Conclusions Close monitoring of anxiety and depression levels in MSM on PrEP is crucial. Provision of targeted mental health support is essential to enhance PrEP effectiveness.